GENERAL LINGUISTIC PROBLEMS OF UZBEK AND KOREAN STUDENTS STUDYING ENGLISH AS A SECOND LANGUAGE AND THEIR SOLUTIONS - Gulbakhor Nazirkulova Muhitdin qizi (Web of Journals Publishing, 2025)
In this article, the general linguistic problems facing Uzbek and Korean students studied as a second language will be analyzed. In particular, phonetic, grammatical and local difficulties are considered and methods to effectively eliminate them. Students' pronunciation difficulties, grammatical errors, and the problems in increasing vocabulary problems are considered by the global. The effectiveness of teaching methods based on interactive methods, modern technologies and contexts is discussed. The results of the study can be beneficial in teaching individual and general approaches to teaching the English language.
Keywords: Learning as a second language, linguistic problems, phonetics, grammar, Uzbek students, Korean students, interactive methods, pedagogical approaches.